Optimized Ensiling Conditions and Microbial Community in Mulberry Leaves Silage With Inoculants - Cui, Xiaopeng; Yang, Yuxin; Zhang, Minjuan; Jiao, Feng; Gan, Tiantian; Lin, Ziwei; Huang, Yanzhen; Wang, Hexin; Liu, Shuang; Bao, Lijun; Su, Chao; Qian, Yonghua (Frontiers in Microbiology, 2022)
Mulberry leaves (ML) are a promising alternative fodder source due to their high protein content and the abundance of active components. A test of three inoculants in various combinations revealed that high quality ML silage was produced at an inoculum ratio of 1:1:0 (50% Saccharomyces cerevisiae, 50% Lactobacillus plantarum and 0% Bacillus subtilis). Using dry matter (DM) loss, pH, ammonia-N and amino acid contents, total antioxidant activity, and total flavonoids content to evaluate silage quality, this inoculant mixture was shown to produce high quality silage within a range of inoculum size (5–15%), moisture contents (50–67%), ensiling temperatures (27–30 °C),and ensiling duration (14–30 d). A third trial comparing silages produced after 30 d at 28 °C and 50% moisture content revealed that silage E, prepared using a L. plantarum inoculant alone, displayed the lowest DM loss and pH, low bacterial diversity, and was dominated by Lactobacillus (88.6%), with low abundance of Enterobacter (6.17%). By contrast, silage B5,prepared with equal ratios of L. plantarum and S. cerevisiae, was dominated by Enterococcus (67.16%) and Lactobacillus (26.94%), with no yeast persisting; reducing DM content from 50% to 40% altered these relative abundances to 5.47, 60.61, and 0%, respectively. Control silages produced without an inoculant had the highest pH and ammonia-N content (indicative of poor quality) and lowest anti-oxidant activity, had higher bacterial diversity, and were dominated by Carnobacterium (74.28%) and Enterococcus (17.3%). In summary, ensiling of ML conditions with proper inoculants yielded high-quality silage with a favorable microbial community composition.